Clinical Outcomes of Noninvasive Ventilation in Asthma, Bronchiectasis, and Other COPD. Issue 12 (December 2021) - Nemeh, Christopher; Dongarwar, Deepa; Oguduwa, Emmanuella; Salihu, Hamisu M.; Barrantes Perez, Jairo
Abstract : Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality and disability worldwide. Use of noninvasive ventilation appears to be associated with a significant decrease in the frequency of exacerbation, hospital admissions, and mortality in patients with COPD. In this study, the authors seek to determine clinical outcomes, prevalence, patient profiles, and systems characteristics associated with the use of noninvasive ventilation in patients with asthma, bronchiectasis, and other COPD. Supplemental digital content is available in the text. Abstract: Objectives: Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality and disability worldwide. Use of noninvasive ventilation (NIV) appears to be associated with a significant decrease in frequency of exacerbation, hospital admissions, and mortality in patients with COPD. In this study, we sought to determine clinical outcomes, prevalence, patient profiles and systems characteristics associated with the use of NIV in patients with asthma, bronchiectasis, and other COPD. Methods: In this retrospective study, the Nationwide Inpatient Sample dataset was used to evaluate patient characteristics for adult hospitalizations for asthma, bronchiectasis, and other COPD between January 2002 and December 2017. Using the adjusted survey logistic regression model, the association between NIV and in-hospital mortality for asthma, bronchiectasis, and other COPD was ascertained. Results: Other COPD hospitalization prevalence was nearly two times higher among non-Hispanic Black patients compared with non-Hispanic White patients (8.32/1000 vs 4.46/1000). There was a 4.3% average annual decrease in the rates of NIV among hospitalized patients with other COPD during the study period. Furthermore, nonusage of NIV was associated with increased in-hospital mortality for asthma (odds ratio [OR] 1.53, 95% confidence interval [CI] 1.50–1.57), bronchiectasis (OR 2.01, 95% CI 1.69–2.41), and other COPD (OR 1.24, 95% CI 1.16–1.32), respectively. Conclusions: Inpatient use of NIV has a clear mortality benefit in asthma, bronchiectasis, and COPD. These findings support a signal for potential benefit, particularly among certain populations and warrant further investigation.